The relationship between serum level of matrix metalloproteinase-7 and interstitial lung disease in patients with systemic sclerosis - Mervat M Abo Gabal; Noha H Shedid; Elham S Mohamed; Warda Abdelfattah (SpringerOpen, 2019)
Background Interstitial lung disease (ILD) remains a leading cause of mortality in systemic sclerosis (SSc). Matrix metalloproteinases (MMPs) play an important role in inflammation, autoimmune diseases and aberrant fibrotic tissue remodeling. Aim The aim of this work was to evaluate the relation between serum level of MMP-7 and ILD in SSc patients. Patients and methods The study was conducted on 30 SSc patients. Pulmonary function tests and chest high-resolution computed tomography were assessed. Degree of fibrosis was assessed according to Warrick severity and extent scores. Serum level of MMP-7 was measured. Results The 30 patients had a mean age of 41.60±11.11 years and disease duration of 3.50±1.81 years; 23 with diffuse and seven with limited subtype. ILD was present in 20 patients. Serum MMP-7 was significantly higher in those with ILD (412.5±52.4 ng/ml) compared with those without (disease control group) (351.4±56.4 ng/ml) (P=0.007). In patients with ILD, MMP-7 was significantly higher in those with ground-glass opacities, honeycombing and reticular infiltration on high-resolution computed tomography; yet, it was comparable among the different grades of pulmonary restriction by pulmonary function test. There was a significant negative correlation between serum MMP-7 level and forced vital capacity and forced expiratory volume in one second (r=−0.46, P<0.05 and r=−0.65, P<0.0001, respectively). Correlations between MMP-7 and Warrick severity and extent were significant (P=0.002 and 0.007, respectively). MMP-7 at a cut-off value of 367.4 ng/ml was 85% sensitive and 80% specific for detection of ILD. Conclusion There is a strong association between serum MMP-7 and the presence, severity and extent of ILD in scleroderma patients. It might be a useful marker for ILD in SSc.